An Estimation of Multiphase Relative Permeabilities in Reservoir Cores from Micro-CT Data - Ahmed Zoeir; Seyyed Alireza Tabatabaei Nejad; Jafar Ghajar (Journal of Petroleum Science and Technology, 2019)
With significant increase of tomographic equipment power, demand for Prediction relative permeability prediction Predicting in porous media from digital image data. In this work, it is predicted three -phase relative permeabilities with co-applying Darcy’s and Stokes equations in two case studies, namely Bentheimer sandstone and Estaillades limestone which their micro-CT data files were downloaded from Imperial College website. In order to perform calculations firstly we extracted pore connected network from the micro-CT data and it is estimated fluids distribution within pore channels during two-phase flow. Then we calculated pressure distribution of each phase solving its continuity and momentum equations within the obtained connected phase network. Pressure distribution and fixed volumetric flow rate ( that flows through all cross-sections perpendicular to the supposed flow direction), then were applied to solve for effective permeabilities. Effective permeabilities were then related to the relevant saturation and curves of two -phase relative permeabilities were derived in this manner. Stone’s equation was finally applied to estimate three phase permeability ternary curves. Results showed that application of correlations for determining fluid distributions is accurate enough for multiphase relative permeability estimation in real case studies. This paper also shows that performing calculations on the segmented REVs is more accurate than work on simplified pore network models extracted from micro-CT data.